Leveraging Digital Health Technologies and Outpatient Sampling in Clinical Drug Development: A Phase I Exploratory Study. Issue 1 (23rd July 2018) - Dockendorf, Marissa F.; Murthy, Gowri; Bateman, Kevin P.; Kothare, Prajakti A.; Anderson, Melanie; Xie, Iris; Sachs, Jeffrey R.; Burlage, Rubi; Goldman, Andra; Moyer, Matthew; Shah, Jyoti K.; Ruba, Rachel; et al.
Abstract : Merck & Co, Inc (Kenilworth, NJ) is investing in approaches to enrich clinical trial data and augment decision making through use of digital health technologies, outpatient sampling, and real‐time data access. As part of this strategy, a phase I study was conducted to explore a few technologies of interest. In this fixed‐sequence two‐period trial, 16 healthy subjects were administered 50‐mg once‐daily sitagliptin packaged in a bottle that electronically captured the date and time study medication was dispensed (period 1) and in a traditional pharmacy bottle (period 2). Dried blood spot samples were collected for sitagliptin concentration analysis on select study days, both in clinic and at home, with collection time recorded using an electronic diary in period 1 and by clinic staff in period 2. Study results demonstrated the feasibility and subject acceptance of collecting digital adherence data and outpatient dried blood spot samples in clinical trials and highlighted areas for future improvements.